The divine comedy : Hell, Purgatory, Paradise - Dante Alighieri, 1265-1321 (Chartwell Books, 2010)
An illustrated edition of the epic poem in which the poet describes his spiritual journey through Hell, Purgatory, and Paradise--guided first by the poet Virgil and then by his beloved Beatrice--which results in a purification of his religious faith.